A short-term evaluation of oral hygiene education methods in fixed orthodontics patients: a randomized clinical trial comparing assistant training, software, and social media - Hooman Shafaee; Sorour Saeedi; Erfan Bardideh; Mahsa Ghorbani; Pooya Saeedi (BMC, 2024)
Abstract Objective To compare the effectiveness of different oral hygiene education strategies on periodontal health in fixed orthodontic patients in a one-month period: assistant-led instruction, social media-based education, and custom-made software. Methods Sixty orthodontic patients from Mashhad University of Medical Sciences' Dentistry School were randomly assigned into three groups. Each group received oral health education differently: via assistant instruction, educational videos on social media, or a researcher-designed software for Android smartphones. After a month, participants' oral health was evaluated using the plaque index (PI) and the gingival index (GI). Results Assistant-led education group demonstrated the highest PI (1.26 ± 0.70) and GI (0.92 ± 0.67), while the software group reported the lowest indices (PI = 0.68, GI = 0.46 ± 0.46). The social media group's measurements fell between these extremes (PI = 0.89 ± 0.75, GI = 0.60 ± 0.52). Significant group differences were found for both PI and GI (P = 0.028 and P = 0.047, respectively). Pairwise comparison revealed significantly lower PI and GI in the software group compared to the assistant group. No significant differences were found between the social media and other groups. Conclusion Our results suggest that the use of specially designed software could be the most effective strategy for improving oral hygiene in orthodontic patients. Meanwhile, traditional assistant-led education showed the least effectiveness. The study supports the potential benefit of utilizing digital tools, such as bespoke software and social media, in oral health education for orthodontic patients. Trial registration The study was registered in the Iranian Registry of Clinical Trials (IRCT) database with the identification code IRCT20200609047705N2 in 13.07.2021.